The Influence of the External Auditor's Critical Thinking Skills on the Report's Quality - Ameen, Iman Baqer; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2024)
The main aim of this study was to determine a relationship between the critical thinking skills of auditors and the caliber of their reports. The objective was to improve the auditors' expertise in this cognitive field, evaluate its effect on their professional competence, and analyze its influence on their capacity to express opinions. A descriptive-analytical technique was utilized to accomplish the study's goals. The research hypotheses were evaluated using simple linear regression analysis, precisely the least squares method. This goal was achieved using the SPSS v.26 program. To meet the research inquiries, the researchers developed a questionnaire with two dimensions to collect data. The core framework for the analytical thinking of an external auditor comprises four key aspects: inductive reasoning, deductive reasoning, exploratory thinking, and problem-solving thinking. The study sample comprised 205 individuals, including 113 auditors from the Federal Board of Financial Supervision and 92 auditors from auditing offices and enterprises in Iraq. The study's findings suggest a positive association between the independent variable, critical thinking skill, and the dependent variable, the quality of the report. This is because most auditors in the Board of Financial Supervision affirm that auditors from the federal and audit offices demonstrate curiosity and apply professional skepticism at every stage of the audit process. This exemplifies their aptitude for employing inductive reasoning and constructing. Nevertheless, they can produce inventive concepts that efficiently tackle work-related difficulties. Furthermore, the task of identifying appropriate solutions is complex, often necessitating the use of electronic programs to tackle challenges faced during the auditing of electronic systems effectively. The respondents agreed that the auditor's proficiency in critical thinking will improve the quality of the report he produces.